Involvement of Netrins and Their Receptors in Neuronal Migration in the Cerebral Cortex - Yamagishi, Satoru; Bando, Yuki; Sato, Kohji (Frontiers in Cell and Developmental Biology, 2021)
In mammals, excitatory cortical neurons develop from the proliferative epithelium and progenitor cells in the ventricular zone and subventricular zone, and migrate radially to the cortical plate, whereas inhibitory GABAergic interneurons are born in the ganglionic eminence and migrate tangentially. The migration of newly born cortical neurons is tightly regulated by both extracellular and intracellular signaling to ensure proper positioning and projections. Non-cell-autonomous extracellular molecules, such as growth factors, axon guidance molecules, extracellular matrix, and other ligands, play a role in cortical migration, either by acting as attractants or repellents. In this article, we review the guidance molecules that act as cell–cell recognition molecules for the regulation of neuronal migration, with a focus on netrin family proteins, their receptors, and related molecules, including neogenin, repulsive guidance molecules (RGMs), Down syndrome cell adhesion molecule (DSCAM), fibronectin leucine-rich repeat transmembrane proteins (FLRTs), and draxin. Netrin proteins induce attractive and repulsive signals depending on their receptors. For example, binding of netrin-1 to deleted in colorectal cancer (DCC), possibly together with Unc5, repels migrating GABAergic neurons from the ventricular zone of the ganglionic eminence, whereas binding to α3β1 integrin promotes cortical interneuron migration. Human genetic disorders associated with these and related guidance molecules, such as congenital mirror movements, schizophrenia, and bipolar disorder, are also discussed.